(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
In this study, poly(lactic acid) (PLA) and silk fibroin(SF)-gelatin were sequentially electrospun on the collector to prepare the PLA/SF-gelatin composite fiber membranes. Scanning electronic microscope (SEM) was used to observe the morphology of the membranes. The microstructure of the fiber membranes before and after treatment with methanol was characterized using Fourier transform infrared (FTIR) and differential thermal analysis (DTA), and then the effects of the microstructure change on the mechanical properties, dissolution rate and shrinkage were evaluated. Furthermore, SEM and MTT assays were preformed to assess the proliferation and adhesion of 3T3 mouse fibroblasts cultured on the PLA/SF-gelatin scaffolds. After chemical treatment with methanol, the findings suggested the microstructure of PLA fiber did not change obviously, whereas the β-sheets of SF and α-helix structures of gelatin in SF-gelatin blend nanofibers increased, consequently the diameter of electrospun PLA/SF- gelatin membranes, the dissolution rate declined by 64%, the strain at break electrospun PLA/SF-gelatin scaffolds, the shrinkage of the PLA/SF -gelatin composite scaffolds caused by chemical treatment decreased by 40%. The cells adhered on to the surface of blend layer fibers and formed a confluent monolayer after 12 days cultivation. The good mechanical properties and dimensional stability of the chemically treated PLA/SF -gelatin scaffolds, combined with the ability to support cell growth in vitro, suggested tremendous potential application in tissue engineering.